Fun English To Increase Vocabulary And Motivation For Kindergarten Children Of Santa Rita Cassia, Kefamenanu-TTU - Thresia Trivict Semiun; Maria Wihelmina Wisrance; Chatarina Gradict Semiun; Oktovianus Edvict Semiun (Universitas Tanjungpura, 2022)
Community service was done as a concrete implementation of NTT Provincial Governor Regulation No. 56 2018. Following the adoption of the regulation, the team considered that it was necessary to promote the importance of English for the NTT community, especially for young children. As a Lingua Franca, English plays an important role; yet English language teaching is currently limited to lessons in class only without the assistance of its usage outside the classroom. The team believes it was a need to carry out a community service movement such as teaching that was more focused on the use of English language skills as early as possible. Introducing English to children from an early age was expected to improve the quality of the younger generation, especially in the language field. The method of implementing this community service was a teaching method by using children's songs and flashcards. The teaching was done face-to-face. The community service activities were run well and smoothly.